Effect of proton irradiation on electrical properties of a-As2S3 - Gautam, Sanjeev; Thakur, Anup; Shukla, D. K.; Shin, H. J.; Chae, Keun Hwa; Singh, K. P.; Goyal, Navdeep (ELSEVIER SCIENCE BV, 2011)
This paper reports the effect of proton irradiation on the electrical properties of a-As2S3 in the temperature range of 323-418 K and frequency range 0.1-100 kHz. The variation of transport property is studied with proton irradiation dose (1 x 10(13) ions/cm(2) and 1 x 10(15) ions/cm(2)). It has been observed that proton irradiation changes the dc conductivity (sigma(dc)), dc activation energy (Delta E-dc) and ac conductivity (sigma(ac)(omega)). The sigma(dc) and sigma(ac) (w) increases with dose of proton irradiation. The value of frequency exponent (s) decreases with the temperature and irradiation dose. These results are explained in terms of change in density of defect states in these glasses. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: THIN-FILMS; CHALCOGENIDE GLASSES; AC CONDUCTION